Prevalence and Risk Factors of HIV Infection among Clients Attending ICTCs in Six Districts of Tamilnadu, South India - Rajeswari Ramachandran; V. Chandrasekaran; M. Muniyandi; K. Jaggarajamma; Anasua Bagchi; Supriya Sahu (AIDS Research and Treatment)
Objective. To assess the HIV serostatus of clients attending integrated counseling and testing centres (ICTCs) in Tamilnadu, south India (excluding antenatal women and children), and to study its association with demographic, socioeconomic, and behavioral risk factors. Design. In a prospective observational study, we interviewed clients attending 170 ICTCs from six districts of Tamilnadu during 2007 utilizing a standard pretest assessment questionnaire. All the clients were tested for HIV with rapid test kits. Multiple logistic regression analysis was used to identify determinants of HIV infection. Results. Of 18329 clients counseled, 17958 (98%) were tested for HIV and 732 (4.1%; range 2.6 to 6.2%) were tested positive for HIV. Median age of clients was 30 years; 89% had never used condoms in their lives and 2% gave history of having received blood transfusion. In multivariate analysis HIV seropositivity was associated with HIV in the family (adjusted odds ratio) (AOR 11.6), history of having sex with sex workers (AOR 2.9), age ≥31 years (AOR 2.8); being married (AOR 2.5), previously tested for HIV (AOR 1.9), illiteracy (AOR 1.7), unemployment (AOR 1.5), and alcoholism (AOR 1.5). Conclusion. HIV seroprevalence being high in ICTC clients (varied from 2.6 to 6.2%), this group should also be included in routine programme monitoring of sero-positivity and risk factors for better understanding of the impact of the National AIDS Control Programme. This would help in evolving appropriate policies and strategies to reduce the spread of HIV infection.